The Effect of Increasing Cooking Oil Prices and Material Export Prohibition Policy Cooking Oil Standard on National Food Security - Rejang Musi Agastya A. S. W; Pujo Widodo; Rudy Laksmono (PT FORMOSA CENDEKIA GLOBAL, 2023)
The phenomenon of rising cooking oil prices is increasingly being felt by the public Indonesia. The surge in the price of cooking oil, which is quite high, will certainly have an impact on the prices of other goods. This impact can occur because of the multiplier effect caused by the continued skyrocketing cooking oil prices. The most felt effect is also an increase in the price of food, which uses cooking oil as an ingredient. Decreasing productivity and increasing demand have resulted in a scarcity of cooking oil. In addition, oil palm, which is known as a plantation crop with various benefits, is also experiencing increased demand from a non-food perspective. The increasing demand for palm oil which is used as biofuel (biofuel) also takes a big contribution to the decrease in the supply of CPO which will be produced into cooking oil. The government issued a ban on crude oil exports, which has been officially stated in the Minister of Trade Regulation (Permendag) Number 11 of 2022, which the government does not consider to be enforced in the long term. Bhima's view is that if Indonesia implements this policy in a sustainable manner, it will receive many protests from countries that need CPO from Indonesia.